2014
DOI: 10.1186/1756-0500-7-472
|View full text |Cite
|
Sign up to set email alerts
|

Geriatrics in medical students’ curricula: questionnaire-based analysis

Abstract: BackgroundDemographic development is accompanied by an increasingly aging society. Concerning medical education, the treatment of older people as well as the scientific research and exploration of ageing aspects in the coming years need to be considered. Aim of the study was to ascertain medical students’ knowledge, interest, and attitudes regarding older patients and geriatric medicine.MethodsEach participant completed a self-designed questionnaire. This questionnaire was based on three validated internationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This differed from a finding in another study which found that frequent contact with an older adult and undertaking courses in ageing significantly increased the interest of students in working with older adults ( 19 , 20 ). Studies have shown that medical students did not have enough exposure to older adult patients during their education and, therefore, did not see the drawbacks of ageing with multimorbidity ( 21 , 22 ). Hence, having a dedicated course, such as HEC, will increase their exposure, skills, and experience at the undergraduate level.…”
Section: Discussionmentioning
confidence: 99%
“…This differed from a finding in another study which found that frequent contact with an older adult and undertaking courses in ageing significantly increased the interest of students in working with older adults ( 19 , 20 ). Studies have shown that medical students did not have enough exposure to older adult patients during their education and, therefore, did not see the drawbacks of ageing with multimorbidity ( 21 , 22 ). Hence, having a dedicated course, such as HEC, will increase their exposure, skills, and experience at the undergraduate level.…”
Section: Discussionmentioning
confidence: 99%